2009
DOI: 10.1016/j.dsr2.2009.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Temporal changes in community composition of heterotrophic bacteria during in situ iron enrichment in the western subarctic Pacific (SEEDS-II)

Abstract: Little is known about the effects of iron enrichment in high-nutrient, low chlorophyll (HNLC) waters on the community composition of heterotrophic bacteria, which are crucial to nutrient recycling and microbial food webs. Using denaturing gradient gel electrophoresis (DGGE) of 16S rDNA fragments, we investigated the heterotrophic

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 65 publications
1
10
1
Order By: Relevance
“…Arrieta et al (2004) also reported relatively stable bacterial community composition inside and outside the iron-enriched patch, during in situ ironfertilization experiment carried out in the Southern Ocean. However, results from this study are similar to those of Becquevort et al (2007), Eldridge et al (2007) and Kataoka et al (2009). Becquevort et al (2007) observed significant difference in bacterial community structure between low-Fe and high-Fe amended microcosms.…”
Section: Effect On Bacterial Community Compositionsupporting
confidence: 88%
See 1 more Smart Citation
“…Arrieta et al (2004) also reported relatively stable bacterial community composition inside and outside the iron-enriched patch, during in situ ironfertilization experiment carried out in the Southern Ocean. However, results from this study are similar to those of Becquevort et al (2007), Eldridge et al (2007) and Kataoka et al (2009). Becquevort et al (2007) observed significant difference in bacterial community structure between low-Fe and high-Fe amended microcosms.…”
Section: Effect On Bacterial Community Compositionsupporting
confidence: 88%
“…However, omics' technologies have revealed that these bacteria harbor adaptive traits that could promote their dispersion beyond low temperature locations (Methe et al, 2005;Cacace et al, 2010). They play fundamental role in biogeochemical cycles and are important biotechnologically for cold adapted enzymes production (Feller &Gerday, 2003).The Roseobacter clade is reported to preferentially use phytoplankton products (Moran et al, 2002;Grossart et al, 2005;Howard et al, 2006) and are often reported during Iron enrichment experiments (Kataoka et al, 2009;Thiele et al, 2012). The members of Bacillus genus are often reported from terrestrial environment.…”
Section: Phylogenetic Characterization Of Dgge Bands From Microcosm Ementioning
confidence: 98%
“…6A), it is possible that they were brought to the water column from reduced sediments. In the clade of Alphaproteobacteria, all 9 sequences clustered with marine Rhodobacteraceae bacteria and none of them related to SAR11, which is considered to be the most abundant phylogenetic group in the sea (Morris et al 2002) and has been detected in the western North Pacific Ocean (Kataoka et al 2009b). The reason that sequences belonging to the SAR11 group were not detected in the present study is very likely due to methodological limitation (Sánchez et al 2009).…”
Section: Phylogenetic Composition Of Bacteria and Archaeacontrasting
confidence: 52%
“…Although Bacteroidetes were not detected in the Oyashio, Kuroshio, and OyashioKuroshio transition regions of the western North Pacific Ocean (Kataoka et al 2009a), they were often observed in the Western Subarctic Gyre during an in situ iron fertilization experiment in summer (Kataoka et al 2009b). From the Bacteroidetes sequences we found, 11 sequences were grouped with uncultured Bacteroidetes clones obtained in Monterey Bay, Arctic Ocean, or with marine Bacteroidetes isolates (Nedashkovskaya et al 2003); 4 other sequences were related to uncultured Flavobacteria clones obtained from the North Sea (Alonso et al 2007).…”
Section: Phylogenetic Composition Of Bacteria and Archaeamentioning
confidence: 87%
“…Flavobacteria and in particular Polaribacter are frequently found in polar waters, especially during phytoplankton blooms (Abell and Bowman, 2005;Straza et al, 2010), including blooms resulting from artificial iron-fertilization experiments (Agawin et al, 2006;Kataoka et al, 2009). Flavobacteria were described to be efficient polymer degraders (Cottrell and Kirchman, 2000), an idea that is supported from recent genomic and proteomic analyses (Williams et al, 2013;Xing et al, 2014).…”
Section: Diverse Bacterial Responses To Iron-induced Phytoplankton Blmentioning
confidence: 61%